941 Post-Operative Outcomes of Patients Undergoing Surgery During the Acceleration Period of COVID-19 Infection. (4th May 2021) - Fifer, H; Coe, P; Geogloman, I; Qaiser, R; Saleh, A; Adair, R; Peter, M; Dobbins, B; Saha, A
Abstract: Introduction: There are concerns around the safety of performing surgery during COVID-19 outbreaks with few sources of robust evidence. Method: We analysed 5020 consecutive patients who underwent surgery during the acceleration phase of COVID-19 at our hospital from 31st January to 13th April 2020. Data were also analysed for all patients who had a COVID-19 positive test result during the same study period. Results: 156 patients (3%) developed COVID-19 symptoms after surgery; 28 patients (<1%) subsequently had a positive swab result. All-cause mortality was 44 patients (0.9%); 33 deaths (75%) were due to non COVID-19 diagnoses. There were no adverse COVID-19 related outcomes in any of the 648 patients who had cancer operations. Of 28 COVID-19 positive patients, 11 died (8 orthopaedic, 2 urology, 1 vascular surgery) of which 10 had an emergency admission; all were over 70 years of age. Recent surgery was not an independent prognostic factor for survival after COVID-19 infection. 12% of positive COVID-19 swabs were from long-stay patients. Conclusions: Of 5020 operative patients, 0.2% died from COVID-19 and most complications were not related to the infection. With careful consideration, surgery can be provided safely during times of COVID-19 outbreaks with particular emphasis on avoiding in-hospital transmission.